Nickel/Cobalt/Manganese Influence to Coulombic/Retention/Capacity Efficiency in Light Electric Vehicle (Lev) Battery Lifecycle: Sistematic Literature Review - Rahmah, Dewi Anisa; Hidayat, Sahrul (Universitas Padjadjaran, 2026)
The global energy transition driven by the challenges of climate change and the mitigation of greenhouse gas emissions has positioned Light Electric Vehicles (LEVs) as a strategic mobility solution in urban environments. The reliability and sustainability of LEV fundamentally depend on the optimization of lithium-ion battery technology, specifically the composition of NCM (Nickel/Cobalt/Manganase) cathode materials. This systematic literature review aims to critically analyze the relationship between the ratio of the elements Ni, Co and Mn to three electrochemical performance metrics, namely specific capacity, Coulombic Efficiency (EC) and capacity retention in the battery life cycle. The PRISMA methodology was applied to identify and screen relevant literature resulting in 12 studies that were included in the analysis. The results of the data review show that there is a fundamental performance dilemma (trade-off) in the NCM cathode. Nickel (Ni) serves as a high specific capacity driver that reaches 220 . However, the proportion of Ni-rich 0.90 to 0.95 is able to increase the sensitivity of the material thereby triggering extreme performance fluctuations and decreased retention due to cation maxing and volumetric instability of the lattice. Meanwhile, Manganase (Mn) and Cobalt (Co) act as structural stabilizers. Mn shows a U-shape performance pattern on EC and retention with a concentration of Mn 0.35 achieves an optimal EC performance of 93%. For Co, a low concentration of 0.05 provides the best balance between EC 93% and capacity retention of 95% although a peak retention point of 98% is achieved at Co 0.15.